UiTM Mukah Bulletin: Inou Dengah UiTM Mukah? 2nd Issue November 2023 - Bohari, Mohamad Musa; Chik, Yahutazi; Kamaruddin, Siti Faridah; Long, Suffina; Juhari, Nur Nadia Qausar; Joseph, Stefanie Natasha Rich (Corporate Communication Unit, UiTM Mukah Campus, 2023)
Coming up with the second issue of ‘Inou Dengah UiTM Mukah?’ has only been made possible through the support of authors and editors, for whom we are eternally thankful. It has been an exciting experience to produce a piece of work that is aimed at highlighting all the happenings at Mukah Campus. We are grateful that the whole process has taught us many things. Among other things, witnessing the different ways coworkers and students celebrate success stories throughout the year made us think about the importance of recognition and acknowledgment. We believe that complimenting and appreciating coworkers and students in all the ways you can for a good job fosters positive relationships, creates a supportive atmosphere, and enhances overall well-being. The significant impact it has would motivate both individuals and communities and show them gratitude, appreciation, and encouragement. Undoubtedly true, it is imperative to recognize every contribution especially when things demand a lot of effort, but not everyone would expect more than just a simple congratulatory note. No matter how good or bad you think you have done, there is always something to be appreciative of.